LEARNING STYLES AND VARIETY OF MATERIALS IN ENGLISH TEACHING AND LEARNING - Fitriani, Fitriani (STIT Ibnu Rusyd Tanah Grogot, 2021)
Applying of Learning styles and variety of materials are the important factors in teaching and learning English. When the teacher wants to teach must be prepare some materials and apply technic to get the students’ gaining. With recognizing about learning styles and variety of materials are very useful for language teachers to prepare and implement the effective and positive influence in teaching and learning English. Understanding the students’ learning style is the best way and technic to maximalise potential of students in learning process. After knowing the students’ learning style, the teacher will consider the best method to apply in the classroom. All students have not same their own learning style for understanding material in teaching and learning English. So the teacher can apply learning style the suitable condition their students and variant materials to get the students’ progress and avoid boring of class situation.